Analysing the Textual Variance in Terry Pratchett's The Carpet People - Hainsworth, Brian (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2022)
This dissertation analyses the textual variance between Terry Pratchett’s two versions of The Carpet People. The dissertation uses the mixed methodology of close and distance reading to highlight the differences between the two versions and examine the reasons behind some of the changes made in the revised version. It focuses on the traditional presentation of the hero, perceptions of Empire using relative and raw frequencies of characters and language to elucidate the alterations to the texts. It also investigates the differences in the use of direct speech and how it is distributed among the main characters and in the early works of Pratchett. An examination of the interplay between dialogue and action is also performed, noting the increase of direct speech and decrease in elements relating to battle.A further experiment is conducted using human annotation to ascertain the differences in the presence of humour between the texts which underscores one of the principal differences between the texts as the older author revised some of the earlier material using his well-established comic fantasy style.
Keywords: Digital Humanities and Culture